Archaeological Ceramic Fabric Attribution Through Material Characterisation—A Case-Study from Vale Pincel I (Sines, Portugal) - Ana S. Saraiva; Mathilda L. Coutinho; Carlos Tavares da Silva; Joaquina Soares; Susana Duarte; João Pedro Veiga (Heritage)
Defining groups of ceramic objects from archaeological excavations is a crucial and primary practice in the study of settlements, providing information related to ceramic technology, provenance, and interactions, among others. This process begins with a macroscopic analysis of each fragment, identifying common features to define ceramic fabrics. Regularly, this procedure requires further analytical techniques to refine the attribution of each ceramic object to the corresponding fabric. The Early Neolithic site of Vale Pincel I in Sines, Portugal, dates to the second and third quarters of the sixth millennium BC. The earliest examples of ceramica impressa, described by patterned impressions on the surface (impresso pottery), in Portugal were found here. These artifacts are indicative of the Western Mediterranean Basin cycle pre-Cardial ceramic tradition. From the numerous Neolithic ceramic fragments discovered at Vale Pincel I, archaeologists identified 42 fragments, categorizing them into 2 main groups (A and B) through visual analysis, while a third group (C) remained unclassified. Group A, thick ceramic body with reddish hues and very friable surfaces; Group B, thin ceramic body with greyish to black shades and a cohesive appearance. With the aim to resolve the classification of group C ceramics, this study uses a multi-analytical methodology, combining Optical Microscopy (OM), Wavelength Dispersive X-Ray Fluorescence Spectroscopy (WD-XRF), and X-Ray Diffraction (XRD). Integrating the analytical data with previously obtained archaeological information, Group C fragments were attributed to Groups A and B, demonstrating the absence of a distinct third group in Vale Pincel I, highlighting the effectiveness of analytical techniques in ceramic studies, and contributing to a deeper understanding of Neolithic ceramic technology in the Western Mediterranean Basin.